Pro-Social Behaviour Analysis of Students through Students’ Organizations - Yayuk Hidayah; Yusuf Faisal Ali; Anis Suryaningsih (JETL (Journal of Education, Teaching and Learning), 2020)
Student organization as a place to develop the talents of the students in the form of aspirations, ideas, and creativity to provide opportunities for students to be able to nurture their sense of organization. In student organizations, students are met with certain conditions that bring on pro-social attitudes. The purpose of this study is to analyze, describe, and assess the pro-social behaviour of students through student organizations. This research is descriptive qualitative research. Collecting data through observation, interviews and documentation. Analysis of the data is done by using the model of Miles and Huberman. This study results that students involved in student organizations have social behaviours such as empathy, social responsibility, and low egocentrism. The factors that affect student Pro-social attitudes are the environment, knowledge and personality. Mankind as the main source in the organization should be able to develop individuals with certain criteria. Coaching intensively and encouragement over the ownership of Pro-social attitudes for students are solutions to the emergence of the smart and good citizen.